Potential Receptors for Targeted Imaging of Lymph Node Metastases in Penile Cancer - van der Fels, Christa A. M. (Diagnostics (Basel), 2020)
Imaging modalities using tumor-directed monoclonal antibodies may be of value to improve the pre- and intraoperative detection and resection of lymph node (LN) metastatic disease in penile squamous cell carcinoma (PSCC). We investigated the expression of prostate-specific membrane antigen (PSMA), vascular endothelial growth factor (VEGF), epidermal growth factor receptor (EGFR) and epithelial cell adhesion molecule (EpCAM) to analyze their potency for diagnostic applications. Antigen expression was determined in primary tumors and LNs with and without metastases of 22 patients with PSCC. The total immunostaining score (TIS, 0–12) was determined as the product of a proportion score (PS, 0–4) and an intensity score (IS, 0–3). EGFR and VEGF expression were high in primary tumor (median TIS 8) and LN metastases (median TIS 6 and 8, respectively). No EGFR expression was seen in LNs without metastases. However, LNs without metastases did show VEGF expression (median TIS 6). No EpCAM or PSMA expression was seen in PSCC. This study shows that VEGF and EGFR expression is moderate to high in LN metastases of PSCC. Both VEGF and EGFR warrant further clinical evaluation to determine their value as a target for pre- and intraoperative imaging modalities in the detection of LN metastases in PSCC.